The relationship between NAFLD with diet and exercise: Current perspectives - Fariba Aghaei (Journal of Exercise & Organ Cross Talk, 2022)
NAFLD, a general term that describes several diseases caused by hepatic fat deposition such as hepatic steatosis (HS) and nonalcoholic steatohepatitis (NASH), includes the many conditions that are related to fat accumulation in the liver. Indeed, NAFLD is treated with a treatment plan consisting of weight loss, nutritional supplementation, and physical activity. Despite the lack of scientific research on diet and physical exercise, there is a paucity of evidence on NAFLD. The DASH and Mediterranean diets have been frequently used for treating cardiovascular metabolic risk factors, such as insulin resistance and type 2 diabetes mellitus (T2DM). In this study, an in-depth assessment of existing dietary and physical activity methods, involving Brazilian and other country-specific recommendations was conducted to determine their effect on the risk of nonalcoholic fatty liver disease (NAFLD).